(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article describes in detail the issues of distance learning for state teachers, methods, importance, problems of organizing a distance learning system, distance learning models and their types. In addition, the advantages of using modern educational technologies are highlighted and feedback is given on effective ways to use video lessons and multimedia programs in distance learning for state teachers.In distance learning, the student and the teacher are in constant communication with each other using spatially separated training courses, forms of control, electronic communication and other Internet technologies.